Keyword search for doa retrieval using N-gram / Anis Safuraa Ahmad Tajudin - Ahmad Tajudin, Anis Safura (2015)
The rapid growth of the Internet has increased the number of stored and available data tremendously for online documents. One of the documents is Doa which is an act of supplication. Doa is derived from Arabic word which means that one asks for the fulfillment of a need or that some harm be removed from him/her. One way to retrieve the appropriate Doa is to construct a prototype to search and retrieve the appropriate Doa. There are some applications that require using the exact match of the keyword search with the words stored in the database. This approach leads to the retrieval of insignificant results. Thus, this project utilizes N-gram method for the search and retrieval process. Various words may have similar meaning and to increase the accuracy of the retrieved result, this project applies the dice and overlap coefficient algorithm to find the synonyms of the searched word. A relational database for the Malay words has been constructed in two table which is title of doa and verse and the prototype to retrieve the Doa in Arabic, its' meaning in Malay and the use of it has been developed. The result is overlap coefficient percentage result better than dice coefficient.